FLORISTIC COMPOSITION, STAND STRUCTURE, DIVERSITY AND BIOMASS OF TREE SPECIES IN LIMESTONE FORESTS AT GUNUNG PAYANG, SARAWAK, MALAYSIA - Rohaiza, Daud; Meekiong, Kalu; Aida Shafreena, Ahmad Puad (Forestry Department Peninsular Malaysia, 2022)
A study was conducted to determine the tree species composition, stand structure, diversity and to estimate biomass at Gunung Payang in the Serian-Padawan-Tebedu limestone areas, Sarawak. Twenty-five plots of 20 m x 20 m (1 ha) were established and all trees with diameter at breast height (DBH) of ≥5 cm were enumerated. A total of 607 individual trees was enumerated and identified to 37 families, 89 genera and 109 species. Euphorbiaceae is the largest family comprises 10 genera and 13 species. Based on stem density, Euphorbiaceae recorded the highest density with 206 individuals/ha. The Importance Value Index (IVi) of Euphorbiaceae was 23.81%. The Shannon-Weiner Diversity Index (H’) indicated a value of 3.81. The total above-ground biomass of trees was estimated at 278.59 t/ha. This study showed that three species were listed as vulnerable by IUCN Red Data Book and their population trends decreased. The floristic composition implies that the study area can serve as a conservation site for the threatened plant species.